The Legal Basis for Negotiations in International Armed Conflicts - Naser, Rasoul; Mahmood, Luma (Journal of Legal Sciences, 2023)
Negotiations are among the best means that countries use to achieve their various objectives in foreign policy, precisely because of the high degree of influence that this tool exerts in this field, and the extent of its link with other peaceful diplomatic means. On the other hand, negotiations represent the best way to move away from the option of war or perhaps settle it. This is mainly related to the efforts of states to employ this method as a method for dealings among themselves, and thus negotiations represent a supreme value that is indispensable for states, as they represent a clear and universally accepted method of work related to the maintenance of peace and security International as a culture in the relations of states among themselves, as it seeks to resolve disputes among the conflicting parties.